Double boosting single atom Fe–N4 sites for high efficiency O2 and CO2 electroreduction. (September 2021) - Yang, Huijuan; Wang, Xingpu; Wang, ShengBao; Zhang, Pengyang; Xiao, Chi; Maleki Kheimeh Sari, Hirbod; Liu, Jihu; Jia, Jingchun; Cao, Bin; Qin, Jian; Xiao, Wei; Zhou, Zhiyou; et al.
Abstract: Metal-N4 single-atom catalysts have emerged as the frontier of catalysis. However, the low metal loading and abundance of single atoms embedded in carbon skeleton hinder their practical application. Herein, we report an effective "trapping and exposing" strategy for constructing single-atom Fe–N4 catalysts with high density of single-atom active sites. The strategy involves the strong binding of metal ions to sucrose (trapping) to prevent the migration and agglomeration of Fe 3+, followed by the introduction of a mesoporous structure using an SBA-15 template to achieve sufficient exposure of the Fe–N4 sites (exposing). The as-prepared catalyst comprises Fe–N4 moieties (10.8 wt%) with a hierarchical structure. Density functional theory calculations reveal that the chelating reaction between sucrose and Fe 3+ ions has a low free energy, resulting in the formation of highly dispersed Fe–N4 single atoms. The single-atom catalyst displays a high peak power density of 0.784 W cm −2 in a H2 –O2 proton exchange membrane fuel cell and achieves an impressive CO current density of 109 A g −1 at negligible overpotentials in a flow cell. This work provides an efficient strategy for designing high-performance single-atom catalysts for practical electrocatalysis applications. Graphical abstract: Image 1 Highlights: The "trapping-and-exposing" strategy of constructing Fe-N4 single atoms with a metal loading of 10.8 wt% is proposed.. H2 -O2 polymer electrolyte membrane fuel cell based on Fe-N-C catalyst displays peak power density of 0.784 W cm -2 . The CO current density of 109 A g -1 is achieved at negligible overpotentials.